In vivo evaluation of the antimutagenic and antigenotoxic effects of beta-glucan extracted from Saccharomyces cerevisiae in acute treatment with multiple doses - Oliveira, Rodrigo Juliano (2013)
Ample evidence suggests that cancer is triggered by mutagenic damage and diets or supplements capable of reducing such incidences can be related to the prevention of neoplasy development or to an improvement in life quality of patients who undergo chemotherapy. This research aimed to evaluate the antimutagenic and antigenotoxic activity of beta-glucan. We set up 8 experimental groups: control (Group 1), cyclophosphamide (Group 2), Groups 3-5 to assess the effect of beta-glucan administration, and Groups 6-8 to evaluate the association between cyclophosphamide and beta-glucan. The intraperitonial concentrations of beta-glucan used were 100, 150 and 200 mg/kg. Micronucleus and comet assays showed that within the first week of treatment beta-glucan presented a damage reduction rate between 100-62.04% and 94.34-59.52% for mutagenic and genotoxic damages, respectively. This activity decreased as the treatment was extended. During the sixth week of treatment antimutagenicity rates were reduced to 59.51-39.83% and antigenotoxicity was not effective. This leads to the conclusion that the efficacy of beta-glucan in preventing DNA damage is limited when treatment is extended, and that its use as a chemotherapeutic adjuvant need to be better clarified.